Functional and phylogenetic diversity explain different components of diversity effects on biomass production. Issue 8 (8th May 2020) - Huang, Mengjiao; Liu, Xiang; Cadotte, Marc W.; Zhou, Shurong
Abstract : The Anthropocene is defined by human‐driven environmental change, with one consequence being the modern dramatic decline in biodiversity globally. This is especially worrisome given the long‐acknowledged causal linkage between biodiversity and ecosystem functioning and the delivery of ecosystem services. However, the exact mechanisms driving biodiversity–ecosystem function (BEF) relationships remain unclear, specifically the linkages between species differences, measured by trait and phylogenetic distances, and how interactions, such as competitive inequality and stable coexistence via niche partitioning, influence these relationships. Using complementary plant biodiversity experiments, a synthetic‐assembled one that combined species in different phylogenetic distance treatments with a semi‐natural functional group removal experiment, we assessed how species differences influence the mechanisms underpinning BEF relationships. We calculated the net biodiversity effect (ΔY) of biomass production and partitioned it into two additive parts: the complementarity and selection effects at species and functional group level to test how phylogenetic diversity and functional diversity capture the influences of the complementarity and selection effects. For both experiments, we found that phylogenetic and functional diversity explained biodiversity effects through similar mechanisms, with a positive relationship with the complementarity effect, and a negative relationship with the selection effect. However, we found that the selection effect was best predicted by a negative relationship with functional dispersion (FDis ) of height where the selection effect was strongest in plots with similarly tall species and weakest with a greater diversity of heights, while higher complementary effects were best explained by increasing phylogenetic diversity (i.e. high MPDa ). Our work revealed that the mechanisms underpinning biodiversity–ecosystem function relationships are dependent on species differences and how these differences influence competitive inequalities and niche differences.